Bioefficacy of novel insecticides against Bihar hairy caterpillar, Spilarctia obliqua - Devi, Naorem Ibemu; Srivastava, R P (Indian Journal of Plant Protection, 2020)
An experiment was conducted to study the bioefficacy of fipronil (Regent 5SC), lambda-cyhalothrin (Wrestler 5EC) and imidacloprid (Imidatox 17.8 SL) against eight and 11 days old larvae of Spilarctia obliqua by leaf dip method. LC50 values of lambda-cyhalothrin against eight days old larvae were 0.018, 0.0131 and 0.0097% at 12, 24 and 36 h after feeding (HAF), respectively. LT50 and LT90 values of lambda-cyhalothrin @ 0.006% were 39.0 and 129.8 h, respectively. The LC50 value of fipronil against 11 days old larvae at 36 and 48 HAF was 0.093 and 0.073%, respectively. Another experiment on bioefficacy against 13 days old larvae of S. obliqua by residue contact method revealed LC50 values of spinosad (Tracer 45 SC) as 0.147, 0.105, 0.096 and 0.078% at 5, 6, 7 and 8 days after exposure (DAE); and of chlorfluazuron (Atabron 5.4 EC) as 0.151, 0.106 and 0.081% at 6, 7 and 8 DAE, respectively.The highest RT value was reflected by spinosad at LC50 (1.43 times) and LC90 (1.36 times). The LT50 values for chlorfluazuron and spinosad were 6.06 and 5.13 days @ 0.15%; and 4.01 and 3.30 days @ 0.25%,respectively. Spinosad, therefore, was relatively faster in action (1.2 times) than chlorfluazuron.